Molecular and phylogenetic analyses of a calcium/calmodulin-regulated microtubule motor protein from diverse photosynthetic eukaryotes - Abdel-Ghany, Salah Esmat, author; Reddy, A. S. N., advisor; Ranu, Rajinder S., committee member; Stack, Steve, committee member; Kugrens, Paul, committee member (Colorado State University. Libraries, 2001)
The kinesin-like calmodulin (CaM) binding protein (KCBP), a minus end-directed microtubule (MT) motor protein was previously cloned and characterized from dicot species. Like other members of the kinesin superfamily, KCBP has three domains (tail, stalk, and motor). KCBP is unique among all known kinesin-like proteins (KLPs) in having a myosin tail homology 4 domain and talin-like domain (present in some myosin) and a calmodulin-binding domain (CBD). The activity of KCBP has been shown to be negatively regulated by Ca2+/CaM. Genetic studies have indicated a role for KCBP in trichome morphogenesis. In addition, immunolocalization and microinjection studies with KCBP-specific antibody suggest a role for KCBP in plant cell division. Orthologs of KCBP have not been found in the completely sequenced genome of Drosophila melanogaster, Caenorhabditis elegans. and Saccharomyces cerevisiae. The involvement of KCBP in plant-specific functions and its absence in animals and fungi suggest that KCBP is a plant-specific motor protein. To investigate the origin and evolution of KCBP, I used various molecular approaches to clone and characterize KCBP orthologs from phylogenetically diverse photosynthetic species, including Zea mays (maize), a highly evolved flowering plant; Picea abies (spruce), a representative member of gymnosperms; a Stichococcus, a member of charaphyte algae, which are thought to be primitive living photosynthetic eukaryotes. Analyses of the structural organization of KCBP genes have shown that KCBP with its characteristic domains is conserved among all studied organisms, suggesting its origin along with or prior to the evolution of plastids. KCBP in all studied organisms is detected by affinity-purified KCBP antibody to the CBD, suggesting the topology conservation of their CBDs. The C-terminal region of KCBP with the motor domain and CBD was cloned into expression vectors and the fusion protein from these constructs was bound to CaM in the presence of Ca2+. Chelation of Ca2+ abolished CaM interaction with KCBP. Although the coding sequences of KCBP are highly conserved, the number, length, and the position of intervening sequences are highly diverged. DNA blot analysis showed that KCBP is a single copy gene in all studied organisms, suggesting that this gene could be used in phylogenetic analysis to study the relationship among photosynthetic eukaryotes.
Keywords: molecular biology; botany